2019
DOI: 10.1177/2473011419s00432
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and Distal Failure Site Analysis in Percutaneous Achilles Tendon Rupture Repair

Abstract: Category: Ankle Introduction/Purpose: Different techniques have been described for Achilles Tendon Rupture repair, but no biomechanical evaluation have been performed separately for proximal and distal suturing techniques.The purpose of this study was to biomechanically analyze 3 proximal and 2 distal suture configurations during a simulated cyclic load and load to failure. It was hypothesized that proximal suturing technique was stronger than the distal one and that the modified double suturing technique was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…In this study, the PARS technique failed predominantly by tendon tearing at the level where the proximal tendon was secured to the testing machine, and by suture failure. Wagner et al 32 reported a higher risk of suture pullout through the distal tendon compared with the proximal tendon.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the PARS technique failed predominantly by tendon tearing at the level where the proximal tendon was secured to the testing machine, and by suture failure. Wagner et al 32 reported a higher risk of suture pullout through the distal tendon compared with the proximal tendon.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Achilles tendon needs to sustain a minimum of 190 N over repeated load cycles and glide 4 cm during the normal gait cycle. 8,17,22 Unfortunately, combined tendon and soft tissue injuries ultimately yield some degree of impairment, even with current methods of composite flap single-stage reconstruction. There can be wide variations in torque loss, ranging from 6.0% to 80.0% differences between injured and uninjured limbs, in patients undergoing composite flap reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…28 Uma comparação biomecânica do reparo tipo PARS com o "mini-open" utilizando apenas suturas não bloqueadas constatou que o PARS teve maior força em termos de carregamento cíclico e carga até a falha. 29 Uma grande série recente comparando 101 PARS e 169 reparos tradicionais abertos de Aquiles relatou que o reparo tipo PARS apresentou tempos operatórios significativamente mais curtos e um número maior de pacientes capazes de retornar às atividades físicas regulares aos 5 meses após a cirurgia, em comparação com o reparo aberto. A taxa global de complicações pósoperatórias no PARS foi de 5%, enquanto o reparo aberto apresentou 11%, em sua maioria devido às deiscências e infecções.…”
Section: Tratamento Não Cirúrgicounclassified
“…28 Importante ser notado que a literatura também vem favorecendo a reabilitação precoce e funcional, em detrimento da imobilização isolada nas primeiras semanas nos pacientes operados, independentemente da técnica utilizada. 29 Em linhas gerais, o protocolo pós-operatório para ambas as abordagens cirúrgicas, "mini-open" e aberta, é o mesmo. Os pacientes são mantidos em flexão plantar de 20°, ou simétrica ao lado sadio, por 2 semanas.…”
Section: Tratamento Não Cirúrgicounclassified